Seasonal expressions of androgen receptor, estrogen receptors and cytochrome P450 aromatase in the uteri of the wild Daurian ground squirrels (Spermophilus dauricus) - Yu Wang; Ziyi Wang; Wenyang Yu; Xia Sheng; Haolin Zhang; Yingying Han; Zhengrong Yuan; Qiang Weng (European Journal of Histochemistry, 2018)
The reproductive tissues including the uterus undergo dramatic changes in seasonal breeders from the breeding to non-breeding seasons. Classically, sex steroid hormones play important roles in the uterine morphology and functions. To clarify the relationship between sex steroid hormones and seasonal changes in the uterine morphology and functions, the wild Daurian ground squirrels (Spermophilus dauricus) were used as seasonal breeder model. And the immunolocalizations and expression levels of androgen receptor (AR), estrogen receptors α and β (ERα and ERβ) and cytochrome P450 aromatase (P450arom) were investigated in the uteri of the wild Daurian ground squirrels in the breeding (April) and the non-breeding (June) seasons via immunohistochemistry, Western blot and RT-PCR. Histologically, the uterine weight, the thickness of endometrium and the glandular density were significantly higher in the uteri of the breeding season than those of the non-breeding season. In both seasons, the immunostaining of AR was only presented in stromal cells of the uteri; the positive staining of ERα and ERβ were localized in stromal cells and glandular cells; P450arom was merely immunolocalized in glandular cells. The protein and mRNA expression levels of ERα, ERβ and P450arom were higher in the uteri of the breeding season than those of the non-breeding season; conversely, the expressions of AR were higher in the uteri of the non-breeding season comparing with those of the breeding season in both protein and mRNA levels. The AR: ER ratio in the uteri of the non-breeding season exceeded the AR: ER ratio in the uteri of the breeding season in the wild Daurian ground squirrels. These results suggested that seasonal changes in the expression levels of AR, ERs and P450arom might be correlated with the uterine morphology and histology changes, and estrogen may play an important autocrine/paracrine role in regulating the uterine functions of the wild Daurian ground squirrels.